Co-fermentation of acetate and sugars facilitating microbial lipid production on acetate-rich biomass hydrolysates. (May 2016) - Gong, Zhiwei; Zhou, Wenting; Shen, Hongwei; Yang, Zhonghua; Wang, Guanghui; Zuo, Zhenyu; Hou, Yali; Zhao, Zongbao K.
Highlights: Cryptococcus curvatus co-utilizes acetate and sugars for lipid production. Acetate and sugar mixtures can give improved lipid production. Lipid content reached 60.8% on acetate-rich corn stover hydrolysates. Lipid samples had similar fatty acid compositional profiles to those of cocoa butter. Abstract: The process of lignocellulosic biomass routinely produces a stream that contains sugars plus various amounts of acetic acid. As acetate is known to inhibit the culture of microorganisms including oleaginous yeasts, little attention has been paid to explore lipid production on mixtures of acetate and sugars. Here we demonstrated that the yeast Cryptococcus curvatus can effectively co-ferment acetate and sugars for lipid production. When mixtures of acetate and glucose were applied, C. curvatus consumed both substrates simultaneously. Similar phenomena were also observed for acetate and xylose mixtures, as well as acetate-rich corn stover hydrolysates. More interestingly, the replacement of sugar with equal amount of acetate as carbon source afforded higher lipid titre and lipid content. The lipid products had fatty acid compositional profiles similar to those of cocoa butter, suggesting their potential for high value-added fats and biodiesel production. This co-fermentation strategy should facilitate lipid production technology from lignocelluloses.